Live high, train low at natural altitude - Stray-Gundersen, J.; Levine, B. D. (Scandinavian Journal of Medicine & Science in Sports, 2008)
For decades altitude training has been used by endurance athletes and coaches to enhance sea-level performance. Whether altitude training does, in fact, enhance sea level performance and, if so, by what means has been the subject of a number of investigations. Data produced principally by Levine and Stray-Gundersen have shown that living for 4 weeks at 2500 m, while performing the more intense training sessions near sea level will provide an average improvement in sea level endurance performance (duration of competition: 7-20 min) of approximately 1.5%, ranging from no improvement to 6% improvement. This benefit lasts for at least 3 weeks on return to sea level. Two mechanisms have been shown to be associated with improvement in performance. One is an increase in red cell mass (~8%) that results in an improved maximal oxygen uptake (~5%). That must be combined with maintenance of training velocities and oxygen flux to realize the improvement in subsequent sea level performance. We find no evidence of changes in running economy or markers of anaerobic energy utilization. Our results have been obtained in runners ranging from collegiate to elite. Wehrlin et al. have recently confirmed these results in elite orienteers. While there are no specific studies addressing the use of living high, training low in football players, it is likely that an improvement in maximal oxygen uptake, all other factors equal, would enhance football performance. This benefit must be weighed against the time away (4 weeks) from home and competition necessary to gain these benefits.